2016
DOI: 10.20944/preprints201609.0116.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Newborn Care in the Home and Health Facility: Formative Findings for Intervention Research in Cambodia

Abstract: Global coverage and scale up of interventions to reduce newborn mortality remains low, though progress has been achieved in improving newborn survival in many lowincome settings. An important factor in the success of newborn health interventions, and moving to scale, is appropriate design of community-based programs and strategies for local implementation. We report the results of formative research undertaken to inform the design of a newborn health intervention in Cambodia. Information was gathered on newbor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 4 publications
1
6
0
1
Order By: Relevance
“…For example, studies in Bangladesh reported that compliance of family members providing inpatient care ranged between 0% [50] and 3% [34]. Studies on hygiene during neonatal care in the home environment focus primarily on the new mothers or birth attendants [18,23,24,51]. Non-maternal caregivers are not only actively engaged in newborn care in these settings, but they are also important drivers of the mothers' handwashing behaviours [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies in Bangladesh reported that compliance of family members providing inpatient care ranged between 0% [50] and 3% [34]. Studies on hygiene during neonatal care in the home environment focus primarily on the new mothers or birth attendants [18,23,24,51]. Non-maternal caregivers are not only actively engaged in newborn care in these settings, but they are also important drivers of the mothers' handwashing behaviours [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on hygiene during neonatal care in the home environment focus primarily on the new mothers or birth attendants (18,23,24,46). Non-maternal caregivers are not only actively engaged in newborn care, but they are also important drivers of the mothers' handwashing behaviours (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on hygiene during neonatal care in the home environment focus primarily on the new mothers or birth attendants (18,23,24,54). Non-maternal caregivers are not only actively engaged in newborn care in these settings, but they are also important drivers of the mothers' handwashing behaviours (21,22).…”
Section: Discussionmentioning
confidence: 99%